Electro-optic effect in GaN/Al₀.₁₅Ga₀.₈₅N single quantum wells for optical switch - Elkadadra, A.; Abouelaoualim, D.; Oueriagli, A.; Outzourhit, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
he second-harmonic generation (SHG) susceptibility of wurtzite type gallium nitride with single quantum wells has been theoretically investigated in the framework of the compact-density-matrix approach. The confined wave functions and energies of electrons in GaN/AlxGa₁₋xN have been calculated in the effective-mass approximation, solving the Schrödinger equation by Numerov’s method using the second and fourth order approximations for the derivatives. The numerical results for typical GaN/Al₀.₁₅Ga₀.₈₅N quantum wells show that a strong SHG effect can be realized in electric field by choosing some optimized structural parameters.